Mg deficiency interacts with the circadian clock and phytochromes pathways in Arabidopsis. (29th October 2020) - Rivière, Quentin; Xiao, Qiying; Gutsch, Annelie; Defrance, Matthieu; Webb, Alex A. R.; Verbruggen, Nathalie
Abstract: Little is known about the relationship between nutrition and the circadian clock in plants. The first global transcriptomic study in plants of the response to magnesium deficiency (–Mg) revealed that the circadian clock was affected in the Arabidopsis thaliana model species. Interactions between the circadian clock and Mg status were here investigated in the light of recent knowledge. We highlight the wide disturbances caused by –Mg within the central oscillator and, reciprocally, the probable pervasive influence of the circadian clock on the response to –Mg. We provide evidence that light signalling pathways are likely to be involved in the input of Mg status to the circadian oscillator and that they interact with the circadian clock to coregulate an important part of the transcriptomic response. We further studied PIF3 LIKE 1 ( PIL1 ) because it strongly and early responded, before the core genes of the circadian oscillator, and was a representative regulator of light signalling that interacts with the circadian oscillator. Furthermore, the far‐red light‐responsive genes, which are related to PIL1, were more enriched among the –Mg‐deregulated genes than those responding to red, blue and intense lights. Finally, pil1 mutants had an altered response to –Mg notably by losing the upregulation of PSEUDO‐RESPONSE REGULATOR 9, a core circadian oscillator. In short, we have further characterised the interactions between the Mg status and the circadian clock and identified the involvement of light signalling pathways in the response to Mg status. In particular, we have illustrated the role of a light‐signalling component in the regulation of the circadian oscillator and physiological processes during Mg starvation. Abstract : Long‐term magnesium deficiency (–Mg) triggers large disturbances of the transcriptome. We showed that the circadian clock and the phytochromes signalling might play an important role in the regulation of the transcriptomic response to –Mg. These pathways likely interact and regulate many biological processes that are targeted by Mg starvation.